A Closed Queueing Network Approach to the Analysis of Patient Flow in Health Care Systems - Chaussalet, T. J.; Xie, H.; Millard, P. (Methods of Information in Medicine, 2006)
Objectives: To model patient flow in health care systems with bed capacity constraints in order to provide a useful decision aid for health service managers.Methods: We model the patient flow of health care systems using a closed queueing network framework with the assumption that the system is always full. Key performance measures of the health care system are also derived.Results: Using parameters taken from a study of a geriatric department in the UK, we show that the model is useful in helping service managers to gain better understanding of the behaviour of the system. In addition, we demonstrate that the model could help improving decision-making by allowing managers to explore different options and evaluate their impacts on performance. Our findings highlight the importance of policy makers taking into account the interactions between different phases of care.Conclusions: We have developed a novel approach to modelling the flow of patients through health care systems with constrained bed capacity.
Keywords: Patient flow; closed queueing network; system performance evaluation